A variable-capacity-based fuzzy random facility location problem with VaR objective - Wang, Shuming; Watada, Junzo; Shamsul Bahar, Yaakob, Prof. Madya (Springer-Verlag Berlin Heidelberg, 2010)
Link to publisher's homepage at http://www.springerlink.com/